O trabalho cotidiano da gestão escolar : percepções dos diretores da educação infantil da rede municipal de Araraquara - Bertochi, Patrícia Ribeiro Tempesta (2016)
This research has the general objective to analyze the perceptions that school directors from kindergarten in the city of Araraquara / SP have on their own work in order to identify if they understand their eminently pedagogical nature. For this, a qualitative research was done, interpretative type, using questionnaires and semi-structured interview. The data analysis used the triangulation technique, building a profile and an analysis of their perceptions of the pedagogical and administrative activities. For this analysis, the study is based on the concepts of school administration (PARO 2011, 2015); and formation in school management, autonomy and decentralization of education (LÜCK, 2000). It supports also the idea of the need to build a theory for the administration of public school and valorization of the Pedagogic Political Project (SILVA JR, 2015;. VEIGA, 2009). This study deals with, briefly, the subject of education in postmodernity (Hargreaves, 1998), seeking to establish a relationship of social change - democratization of education and the new clientele; crisis of utopias and knowledge; dynamism and access to information - and its new demand for school, changing roles of agents that act on it. This process resulted analytical axes: "Options for career"; "Insertion in school management"; "School director formations" and "Activities undertaken by the director." Data composed the profile of an overloaded professional, devalued, responsible and hamstrung. In relation to its activities directors emphasize pedagogical is not a priority since the purpose of exclusively bureaucratic overlaps them. In the case of directors of early childhood education in Araraquara, this scenario is intensified due to the lack of a team of administrative and pedagogical support. In this respect, there is a devaluation of this level as the other directors of the network, the other levels and programs, which entered the same process with the same requirements, have these agents. Consequently, perceives the hegemonic thought that the school of early childhood education is a guard location and care of children without educational nature. As for the numerous formations made by the directors, none was cited as something significant in aid of their activities, so this research brought contributions to the initial and continuing education, demonstrating the need for dialogue with the everyday working practices of directors, avoiding also a clash with the real beginner’s directors. As for the results, for the Municipal Araraquara and its supervisory staff, the data show the number of documents requested, sometimes with the same data and the difficulty of the director alone, turn to the pedagogical work, and noted the need reframing of this position, due to the working conditions and depreciation already mentioned. The data also showed that this research brought moments of reflection for directors on the roles they play, including raising the request of some of them to create a study group. Finally, for the researcher and supervisor, which in this movement to stop to listen to these managers, its operations and spurred to seek new knowledge and ways of doing things that enable the pedagogical action of directors in schools.